Four cases of parapelvic cyst - Ikemoto, I (Hinyokika kiyo. Acta urologica Japonica, 1983)
Four cases of parapelvic cyst are reported, and 27 clinical cases reported in Japan are reviewed. Three of our four cases were male; two of the three cases were benign prostatic hypertrophy, and one was cholelithiasis. For routine urinary tract examination and for differential diagnosis, excretory urograms were made first. The excretory urograms suggested the presence of these parapelvic cysts. Computed tomography performed immediately, gave clear images of the parapelvic cyst in the kidney. The fourth case was a female patient preoperatively suspected as having a renal malignant tumor associated with hemorrhage, however, this case was postoperatively diagnosed as a parapelvic cyst of the kidney associated with hemorrhage in the cyst. Computed tomography should be considered as one of the most useful methods for the diagnosis of parapelvic cysts